Degradable high-strength medical adhesive as well as preparation method and application thereof
By modifying triols and using raw materials such as isocyanates, a degradable high-strength medical adhesive was prepared, which solved the problem of difficult degradation of existing adhesives in the body and insufficient bonding strength, and achieved efficient and safe tissue bonding effect.
Patent Information
- Application Number
- CN202510112807.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-05-13
AI Technical Summary
Existing medical adhesives are difficult to degrade in the body, which may lead to inflammatory reactions and tissue repair disorders. At the same time, their rapid curability and insufficient adhesive strength limit their application in and out.
A high-strength medical adhesive for degradable high-strength medical use isocyanate and N-methyldiethanolamine modified by polyethylene glycol carboxylic acid derivatives is prepared through the principle of ester bond hydrolysis and the principle of hydrophilic-hydrophobic phase.
This adhesive can degrade rapidly in the body, avoid inflammatory reactions, and has high strength and rapid curing capabilities, which are suitable for the bonding needs of different tissues.
Smart Images

Figure CN119971117A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of biomedical technology, and in particular to a degradable high-strength medical adhesive and a preparation method and application thereof. Background Art
[0002] Currently, invasive methods such as suturing or fixing nails are usually used to close wounds in surgical operations. However, this method cannot completely close the wound and often causes secondary tissue damage or leakage. The use of medical adhesives can not only solve the above problems, but also effectively shorten the operation time and reduce the pain of patients. Therefore, medical adhesives are increasingly widely used in clinical practice.
[0003] At present, the medical adhesives commonly circulated in the domestic and foreign markets are mainly divided into two categories: cyanoacrylate adhesives (CA) and fibrin glue (FS).
[0004] Cyanoacrylate adhesives are a unique type of one-component fast-curing adhesive that was developed decades ago for use in clinical tissue bonding and has been used in more than 1 million clinical cases. It has excellent bonding strength and durability, good antibacterial properties and biocompatibility. When applied on the body surface, the cured film can fall off with the keratinous skin in 7 to 10 days. However, cyanoacrylate adhesives are difficult to degrade after curing, and long-term retention in the body can easily cause inflammatory reactions that inhibit tissue repair, limiting its application in the body; in addition, it cures quickly within a few seconds, making it difficult to align the wound in time or causing incorrect operations, resulting in unsatisfactory results and a poor user experience.
[0005] The main components of fibrin adhesive are adhesion proteins (high concentration of fibrinogen, coagulation factor XIII, fibronectin and plasminogen), thrombin and calcium chloride. It is mainly used to treat bleeding problems after clinical surgery such as fragile tissue, suture bleeding or inability to suture, and produces a coagulation effect by interacting with the body's coagulation system. However, it also has some disadvantages. For example, fibrin glue extracted from mammalian blood is a foreign protein, which may induce human immune response and cause allergies. Bovine aprotinin antibody factor V can cause cross-allergic reactions and can also cause severe bleeding, skin symptoms, fever, respiratory and cardiac arrest and other adverse drug reactions. In addition, fibrin adhesives have low bonding strength and cannot maintain long-term bonding effects, which greatly restricts the application of this type of adhesive in tissue bonding. Summary of the invention
[0006] The purpose of the present invention is to provide a degradable high-strength medical adhesive and a preparation method and application thereof, so as to significantly improve the comprehensive performance of the medical adhesive.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is: The first aspect of the present invention provides a degradable high-strength medical adhesive, which is made by reacting raw materials, wherein the raw materials include component A, component B and component C, wherein component A is triol and its derivatives and / or triol modified by polyethylene glycol carboxylic acid derivatives and its derivatives, component B is isocyanate, amino acid or amino acid derivative, and component C is N-methyldiethanolamine and / or bis(2-hydroxyethyl)-N-methyl-N-trifluoromethylammonium iodide and its derivatives; The molar ratio of -NCO groups in the component B to the total -OH groups in the component A and the component C is 2:1, and the molar ratio of the component A to the component C is (1-9):2.
[0008] Furthermore, the triol is trimethylolpropane; the polyethylene glycol carboxylic acid derivative is a mixture of one or more selected from polyethylene glycol-carboxylic acid, diethylene glycol-carboxylic acid, trimethylene glycol-carboxylic acid and tetraethylene glycol-carboxylic acid; the isocyanate is lysine ethyl diisocyanate and its derivatives or 1,4-diisocyanatobutane and its derivatives.
[0009] Furthermore, the raw materials also include a rheology regulator, a foaming catalyst and a stabilizer. The amount of the rheology regulator is 30-65% of the mass of component B; the amount of the foaming catalyst is 0.07-0.25% of the mass of component B; and the amount of the stabilizer is 0.04-0.13% of the mass of component B.
[0010] Further, the rheology modifier is a mixture of one or more selected from pentafluorobutane, heptafluoropropane and perfluorohexanone; the stabilizer is a mixture of one or more selected from pyruvic acid, dimethyl sulfoxide, propylene glycol methyl ether acetate, triethyl citrate, sulfuric acid, hydrochloric acid and phosphoric acid; The foaming catalyst is at least one selected from an organic amine catalyst and an organic metal catalyst, and the organic amine catalyst is a mixture of one or more selected from triethylenediamine, bisdimethylaminoethyl ether and bismorpholine diethyl ether; The organic metal catalyst is a mixture of one or more selected from stannous octoate, dibutyltin dilaurate, organic bismuth salts and organic antimony salts.
[0011] Furthermore, the method for preparing the triol modified by the polyethylene glycol carboxylic acid derivative comprises the following steps: (1) reacting a polyethylene glycol carboxylic acid derivative with a hydrogen extraction reagent under the action of a first catalyst, and simultaneously introducing a benzyl protecting group to obtain an intermediate product I; (2) reacting the intermediate product I with a triol under the action of a second catalyst and a condensing agent to obtain an intermediate product II; (3) The intermediate product II is subjected to hydrogenation catalysis under the action of a third catalyst to obtain the triol modified with the polyethylene glycol carboxylic acid derivative.
[0012] Furthermore, in step (1), the molar ratio of the polyethylene glycol carboxylic acid derivative, the first catalyst, the hydrogenation reagent, and the benzyl protecting group is (1-2): (1-2): (1-1.5): (1-3); the first catalyst is triethylamine, the hydrogenation reagent is sodium hydride, and the reagent providing the benzyl protecting group is 4-methoxybenzyl chloride; In step (2), the molar ratio of the intermediate product I to the triol, the second catalyst and the condensing agent is 1:(0.2-0.3):(0.2-0.35):(1-1.5); the second catalyst is 4-dimethylaminopyridine; and the condensing agent is 1,3-dicyclohexylcarbodiimide.
[0013] Furthermore, the preparation method of the bis(2-hydroxyethyl)-N-methyl-N-trifluoromethylammonium iodide is to modify N-methyldiethanolamine under the action of a fluorine-containing halogenated hydrocarbon; wherein the fluorine-containing halogenated hydrocarbon is trifluoroiodomethane, and the molar ratio of the N-methyldiethanolamine to the fluorine-containing halogenated hydrocarbon is 1:(1~2).
[0014] The second aspect of the present invention provides a method for preparing a degradable high-strength medical adhesive, comprising the following steps: S1: mixing component A and component C, heating and dissolving them, and then adding the third catalyst and component B to obtain a mixed reaction system; S2: After the reaction is complete, the temperature is lowered, and a rheology regulator, a foaming catalyst and a stabilizer are added to the mixed reaction system. After mixing evenly, the degradable high-strength medical adhesive is obtained.
[0015] Furthermore, in step S1, the mixing heating temperature is 75-85°C, and the heating reaction time is 1-2h; the third catalyst is N,N-methylenebisacrylamide, and the molar ratio of the third catalyst to the component B is 1:(750-1500); in step S2, the cooling temperature is ≤15°C.
[0016] The third aspect of the present invention provides an application of a degradable high-strength medical adhesive in a functional composite material.
[0017] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art: The present invention modifies triols by polyethylene glycol carboxylic acid derivatives, utilizes the principle of ester bond hydrolysis, obtains multi-ester bond compounds, and provides multi-hydrolysis centers. The hydrophilicity of polyethylene glycol is simultaneously combined to increase the speed of water molecules conducting to the inside, accelerating curing; and its three hydroxyl groups can increase the cohesive strength, and the increased ester bonds enable the adhesive to be rapidly hydrolyzed and broken after curing, solving the problem of rapid degradation of the adhesive; Biomass isocyanate is introduced into the adhesive skeleton and is excreted from the body through normal human metabolism as lysine, ethanol and carbon dioxide after degradation. It will not remain in the body for a long time and has good biocompatibility. Through fluorine element hydrophobic technology, using the hydrophilic-hydrophobic phase principle, hydrophobic trifluoromethyl and hydrophilic polyethylene glycol groups are introduced, so that when it is cured, the hydrophilic group transfers water molecules to improve the bonding cohesive strength, and the hydrophobic group promotes the migration of charged molecules to the interface, increasing the interface strength; In addition, by adjusting the amount of bis(2-hydroxyethyl)-N-methyl-N-trifluoromethylammonium iodide to change the charge number at the interface, the interface strength will increase or decrease accordingly to meet the needs of adhesion of different tissues. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Hereinafter, some specific embodiments of the present invention will be described in detail in an exemplary and non-limiting manner with reference to the accompanying drawings. The same reference numerals in the accompanying drawings indicate the same or similar components or parts. It should be understood by those skilled in the art that these drawings are not necessarily drawn to scale. In the accompanying drawings: Figure 1 It is a mass loss curve diagram of the in vitro degradation test provided in the present invention; Figure 2 The cell morphology diagram of the MTT cytotoxicity test provided in the present invention; Figure 3 This is a staining diagram of a tissue section after implantation of the adhesive 28d provided in the present invention. DETAILED DESCRIPTION
[0019] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] Embodiment 1: This embodiment provides a degradable high-strength medical adhesive and a preparation method thereof, comprising the following steps: (1) Preparation of triols modified with polyethylene glycol carboxylic acid derivatives 17.82 g of diethylene glycol-carboxylic acid and 101.19 g of triethylamine were placed in a 250 ml three-necked flask, and the overhead stirrer was turned on for stirring, and the speed was set to 280 rpm. A low-temperature circulating bath was turned on and the temperature was set to 0°C. 2.64 g of sodium hydrogen (NaH) was added and the reaction was continued at 0°C for 2 h. 17.23 g of 4-methoxybenzyl chloride was dissolved in 40 mL of tetrahydrofuran (THF) and then added dropwise to the above mixture. The mixture was stirred at 0°C-25°C and 350 rpm for 3 h. The solvent was removed by rotary evaporation and the viscous product was dissolved in ethyl acetate, washed with acid and alkali, washed with saturated brine, dried, filtered, concentrated, crystallized, and vacuum dried to obtain intermediate product I. 35.55g of intermediate product I, 4.02g of trimethylolpropane and 0.40g of 4-dimethylaminopyridine (DMAP) were placed in a 250ml three-necked flask, THF was added to dissolve the homogeneous phase, recorded as solution A, and the low-temperature circulation bath was turned on to cool to about 4°C, and the stirring speed was 350rpm; 6.81g of 1,3-dicyclohexylcarbodiimide (DCC) was dissolved in 30ml THF, and after the homogeneous phase was dissolved, it was added dropwise to solution A through a constant pressure dropping funnel, and the dropping speed was controlled to 1d / s. After the dropwise addition was completed, the low temperature was maintained for 2h, and then the temperature was naturally raised to room temperature and the reaction was continued for 12-16h. The reaction progress was detected by spot plate. After the reaction was completed, DCC was filtered out, concentrated by rotary evaporation, dissolved in ethyl acetate, washed with acid and alkali, washed with saturated brine, dried, filtered, concentrated, crystallized, and vacuum dried to obtain intermediate product II; 84.30 g of intermediate product II, 9.61 g of methanol and 9.4 g of palladium on carbon were added to a 100 ml three-necked flask, replaced with nitrogen for more than five times, and then hydrogen (H2) was introduced. At room temperature, the stirring speed was 350 rpm, and the reaction was carried out for 24 hours. The palladium on carbon was filtered out, concentrated by rotary evaporation, crystallized, and vacuum dried to obtain polyethylene glycol trimethylolpropane.
[0021] (2) Preparation of bis(2-hydroxyethyl)-N-methyl-N-trifluoromethylammonium iodide 11.91 g of N-methyldiethanolamine and 21.55 g of trifluoroiodomethane were added into a 100 ml three-necked flask, and the mixture was reacted at -40°C and 350 rpm for 12 h to obtain bis(2-hydroxyethyl)-N-methyl-N-trifluoromethylammonium iodide.
[0022] (3) Preparation of biodegradable high-strength medical adhesive 7.24g polyethylene glycol trimethylolpropane and 2.36g bis(2-hydroxyethyl)-N-methyl-N-trifluoromethylammonium iodide were vacuum dried at 50℃ for 2h, the dried polyethylene glycol trimethylolpropane and bis(2-hydroxyethyl)-N-methyl-N-trifluoromethylammonium iodide were placed in a 100ml three-necked flask, 2.59g dimethyl sulfoxide (DMSO) was added, nitrogen was replaced for more than three times, heated and stirred at 75℃ to dissolve the homogeneous phase (dissolution time is about 30min), 12mg N,N-methylenebisacrylamide (BIS) was added and continued to stir for 15min, 13.68g lysine ethyl ester diisocyanate was slowly added dropwise to the above mixed system, after the addition was completed, the reaction was kept warm for 1h, then the temperature was lowered to below 15℃, 11.08g pentafluorobutane was added, stirred until homogeneous, 10.7mg bismorpholine diethyl ether was added, The mixture was stirred for 15 minutes, and then 5 mg of sulfuric acid stabilizer was added and stirred for 30 minutes. The mixture was allowed to stand for defoaming to obtain a light yellow clear viscous liquid, which was a biodegradable high-strength medical adhesive.
[0023] Embodiment 2: The present embodiment provides a degradable high-strength medical adhesive and a preparation method thereof, which is different from Example 1 in that the amount of methanol added is 12.82 g, the amount of polyethylene glycolized trimethylolpropane added is 4.83 g, the amount of bis(2-hydroxyethyl)-N-methyl-N-trifluoromethylammonium iodide added is 4.73 g, the amount of DMSO used is 1.79 g, the amount of pentafluorobutane added is 10.73 g, the amount of bismorpholine diethyl ether added is 7.2 mg, and the amount of sulfuric acid stabilizer added is 5.4 mg.
[0024] Embodiment 3: The present embodiment provides a degradable high-strength medical adhesive and a preparation method thereof, which is different from Example 1 in that the feeding amount of polyethylene glycolized trimethylolpropane is 3.62 g, and 1.01 g of trimethylolpropane is added simultaneously; the isocyanate used is 1,4-diisocyanatobutane, the feeding amount of pentafluorobutane is 5.13 g, the feeding amount of bismorpholine diethyl ether is 4 mg, the feeding amount of sulfuric acid stabilizer is 2 mg, and no DMSO is used.
[0025] Embodiment 4: The present embodiment provides a biodegradable high-strength medical adhesive and a preparation method thereof, which is different from the embodiment 1 in that, in step (3), the feeding amount of bis(2-hydroxyethyl)-N-methyl-N-trifluoromethylammonium iodide is 1.18 g, and 0.45 g of N-methyldiethanolamine is added simultaneously; the feeding amount of BIS is 16 mg, the feeding amount of pentafluorobutane is 9.7 g, the feeding amount of bismorpholine diethyl ether is 7 mg, and no DMSO is added.
[0026] Embodiment 5: The present embodiment provides a biodegradable high-strength medical adhesive and a preparation method thereof. The difference between the present embodiment and the embodiment 1 is that in step (3), bis(2-hydroxyethyl)-N-methyl-N-trifluoromethylammonium iodide is not added, and 0.89 g of N-methyldiethanolamine is added simultaneously; the feeding amount of DMSO is 2.28 g, the feeding amount of BIS is 16 mg, the feeding amount of pentafluorobutane is 8.14 g, the feeding amount of bismorpholine diethyl ether is 7 mg, and the feeding amount of sulfuric acid stabilizer is 7 mg.
[0027] Comparative Example 1 The present embodiment provides a medical adhesive and a preparation method thereof, which is different from the embodiment 1 in that trimethylolpropane is not modified by polyethylene glycol carboxylic acid derivatives, and in step (3), 2.0 g of trimethylolpropane is directly used instead of trimethylolpropane modified by polyethylene glycol carboxylic acid derivatives for reaction; the feeding amount of DMSO is 1.39 g; the feeding amount of BIS is 16 mg; the feeding amount of pentafluorobutane is 8.325 g, the feeding amount of bismorpholine diethyl ether is 6 mg, and the feeding amount of sulfuric acid stabilizer is 6 mg.
[0028] In the present invention, the medical adhesives prepared in the above-mentioned embodiments and comparative examples are tested and characterized for performance, and the specific test methods and results of each performance are characterized as follows: 1. In vitro real-time degradation experiment The reference standard is YY / T 1806.1-2021 Evaluation method for in vitro degradation performance of biomedical materials Part 1: Degradable polyesters.
[0029] The adhesives in Examples 1 to 5 and Comparative Example 1 were cured into films and vacuum dried at 35°C to constant weight. The film mass was 0.3 g / piece. Three parallel samples were set at each time point. Phosphate buffer solution (pH = 7.4) was added and the conical flask was sealed. The conical flask was placed in a 37°C constant temperature incubator for degradation research, and the oscillation frequency was set to 72 rpm. Six time points were set at 0d, 2d, 14d, 21d, 30d, and 60d. The degradation mass loss data is shown in Figure 2. Figure 1 As shown. Figure 1 It can be seen that the mass loss is similar at 2 days, because DMSO enters the degradation solution from the membrane. The mass loss of the adhesive films of Example 1, Example 2, Example 4 and Example 5 after 30 days of degradation is more than 50%, which can basically match the time of tissue repair. Only in Example 3, the proportion of PEGylated trimethylolpropane is small, and the mass loss after degradation is small. The degradation without adding PEGylated trimethylolpropane (i.e., Comparative Example 1) is the slowest, and the mass loss after 30 days is only 33%. After 60 days of degradation, the mass loss of Example 1, Example 2, Example 4 and Example 5 exceeds 65%, and the degradation is basically complete.
[0030] 2. Colloid curing time test Refer to GB / T 13477.5-2002 Test Methods for Building Sealing Materials - Determination of Surface Drying Time Method B for curing time test. Cut two pieces of qualitative filter paper and place them on the bottom and top of a 30mm glass dish respectively, add purified water to moisten until no purified water drips out. Squeeze 0.4g of product onto the filter paper, level it naturally, and place it in a 37℃ incubator for a period of time. Then wipe the end of the finger with anhydrous ethanol and gently touch the sample at three different locations. Repeat the above operation at appropriate intervals until no sample adheres to the finger, and record the time. The experimental results are shown in Table 1: Table 1 Curing time 3. Mechanical testing 3.1 Lap-shear tensile bearing strength test According to the YY / T 0729.1-2009 standard, fresh pig skin with fat removed is cut into 25mm×100m size, wrapped with wet gauze soaked in phosphate buffer (PBS, PH=7.2), and placed in a 37℃ water bath or environmental chamber for 30 minutes. When preparing the sample, after applying the adhesive, a force of 2N is applied to the bonding point, and the curing time is 30 minutes. Calculate the average lap-shear tensile bearing strength of 10 parallel samples.
[0031] 3.2 Tensile strength According to the YY / T 0729.3-2009 standard, fresh pig skin with fat removed was cut into 25mm×25mm size, wrapped with wet gauze soaked in phosphate buffer (PBS, PH=7.2), and placed in a 37℃ water bath or environmental chamber for 30min. When preparing the sample, the pig skin was first fixed on the test mold with cyanoacrylate glue, and then the adhesive was applied. A force of 2N was applied during curing, and the curing time was 30min. The tensile strength of 10 parallel samples was calculated.
[0032] The mechanical test results are shown in Table 2: Table 2 Mechanical strength It can be seen from Table 2 that the bonding strengths in the embodiments are all relatively high. From the data of Examples 1, 4, and 5 in the experimental results, it can be seen that bis(2-hydroxyethyl)-N-methyl-N-trifluoromethylammonium iodide has an obvious effect on improving the mechanical properties of the adhesive. The higher the ratio of bis(2-hydroxyethyl)-N-methyl-N-trifluoromethylammonium iodide to N-methyldiethanolamine added, the greater the mechanical strength.
[0033] 4. Elongation at break test Take 0.6 g of the adhesive of Examples 1, 3 and Comparative Example 1, evenly spread it on the agar culture medium, transfer it to a 37°C incubator to cure for 4 hours, peel it off and cut it into strips with a size of 60 mm×20 mm; calculate the tensile strength of 3 parallel samples, and the experimental results are shown in Table 3.
[0034] Table 3 Elongation at break The experimental results show that compared with cyanoacrylate adhesives, the elongation at break of the adhesives in the above embodiments is significantly improved, all exceeding 40%. This is because the polyethylene glycolized trimethylolpropane in the adhesive is connected to the flexible segmented polyethylene glycol, which not only improves the toughness after curing, but also reduces the stiffness, which can match the needs of different tissues.
[0035] 5. In vitro cytotoxicity assay Referring to the requirements of GB / T 16886.5 "Biological Evaluation of Medical Devices" Part 5: In vitro Cytotoxicity Test, L929 was selected as the test cell line, and Examples 1-4 were solidified into films. The sample mass was about 0.3 g. After the samples were sterilized, they were placed in a culture medium to prepare a test extract. The extract was used to culture cells for 24 hours, and the cell survival rate was detected by the MTT method. The average value of each group of results was taken. The cell morphology after culture in the adhesive extract of Examples 1 to 4 is as follows Figure 2 shown.
[0036] Table 4 Statistical analysis of cell survival rate data According to the cell survival rate data analysis in Table 4, the adhesive materials of Examples 1 to 4 all showed good cell compatibility. Compared with the negative control, cell growth was not affected, the cell survival rates were all above 90%, and there was no potential cytotoxicity.
[0037] 6. In vivo implantation experiment Referring to the YY / T1576-2017 tissue engineering medical device product absorbable biomaterial implantation test, ordinary New Zealand white rabbits were taken, weighed, anesthetized, and the hair above the nasal bone was shaved, and the skin was prepared with iodine disinfection. Use a scalpel to make an incision along the midline of the nose, use a 0.6cm circular bone drill to drill a hole at the midline of the nose 40mm away from the rabbit's nose, remove the bone piece covering the nasal septum, use tweezers to separate the nasal septum mucosa from the nasal septum cartilage, and then use microscissors to cut the separated cartilage to a length and width of 5mm×5mm. Use a sterile syringe to absorb 0.05ml of glue from Example 1 and inject it into the position where the cartilage is removed. Fix the mucosa on both sides with microscopic hemostatic clips, record the complete curing time, remove the hemostatic clips, put the covering bone piece back, and close the wound. Three parallel test samples were tested in each group.
[0038] The rabbits were dissected 28 days after implantation, and the nasal septum mucosa and cartilage in the surgical area were removed and stained with HE and Giemsa, and the tissue sections were observed.
[0039] See also Figure 3 Under the microscope, adhesive material (red triangle) is seen below the cartilage tissue (green triangle); the surface of the cartilage and adhesive material is nasal mucosa, and the mucosal epithelium is intact (red arrow); epithelial cells (black arrow) are seen in and around the adhesive material.
[0040] The staining results showed that the mucosa recovered well after 28 days without significant inflammatory reaction, and epithelial cells entered the adhesive material, indicating that Example 1 was helpful for the fixation and repair of mucosal tissue and had good tissue compatibility.
[0041] In summary, the degradable high-strength medical adhesive and its preparation method and application provided in the present invention have the following advantages: (1) By modifying the triol with polyethylene glycol-carboxylic acid derivatives, not only can the ester bond be added to greatly shorten the degradation time, but the hydrophilicity of polyethylene glycol can also be used to accelerate the curing of the adhesive. By adjusting the proportion of the added polyethylene glycol triol, the degradation time of the adhesive can be controlled so that the degradation of the adhesive better matches the repair time of different tissues.
[0042] (2) By changing the content of polyethylene glycol groups, which can transfer moisture to the interior, different contents can change the rate at which moisture is transferred to the interior when the adhesive is cured, thereby adjusting the curing time of the adhesive.
[0043] (3) By increasing the water-repellent groups through N-methyldiethanolamine, when water enters the interior through the polyethylene glycol groups and solidifies, the charged molecules are transferred to the interface to form a hierarchical structure, thereby increasing the interfacial bonding strength. The bonding strength of the adhesive can also be adjusted by changing the proportion of bis(2-hydroxyethyl)-N-methyl-N-trifluoromethylammonium iodide added to meet the needs of different environments.
[0044] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the contents of the present invention and implement them accordingly. They cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A degradable high-strength medical adhesive, made by reacting raw materials, the raw materials comprising component A, component B and component C, characterized in that: The component A is a triol and its derivatives and / or a triol modified by a polyethylene glycol carboxylic acid derivative and its derivatives, the component B is an isocyanate, an amino acid or an amino acid derivative, and the component C is N-methyldiethanolamine and / or bis(2-hydroxyethyl)-N-methyl-N-trifluoromethylammonium iodide and its derivatives; The molar ratio of -NCO groups in the component B to the total -OH groups in the component A and the component C is 2:1, and the molar ratio of the component A to the component C is (1-9):
2.
2. The degradable high-strength medical adhesive according to claim 1, characterized in that: The triol is trimethylolpropane; The polyethylene glycol carboxylic acid derivative is a mixture of one or more selected from the group consisting of mono-polyethylene glycol-carboxylic acid, di-polyethylene glycol-carboxylic acid, tri-polyethylene glycol-carboxylic acid and tetra-polyethylene glycol-carboxylic acid; The isocyanate is ethyl lysine diisocyanate and its derivatives or 1,4-diisocyanatobutane and its derivatives.
3. The degradable high-strength medical adhesive according to claim 2, characterized in that: The raw materials also include a rheology regulator, a foaming catalyst and a stabilizer. The amount of the rheology regulator is 30-65% of the mass of -NCO in the isocyanate; the amount of the foaming catalyst is 0.07-0.25% of the mass of -NCO in the isocyanate; and the amount of the stabilizer is 0.04-0.13% of the mass of -NCO in the isocyanate.
4. The degradable high-strength medical adhesive according to claim 3, characterized in that: The rheology regulator is a mixture of one or more selected from pentafluorobutane, heptafluoropropane and perfluorohexanone; the stabilizer is a mixture of one or more selected from pyruvic acid, dimethyl sulfoxide, propylene glycol methyl ether acetate, triethyl citrate, sulfuric acid, hydrochloric acid and phosphoric acid; The foaming catalyst is at least one selected from an organic amine catalyst and an organic metal catalyst, and the organic amine catalyst is a mixture of one or more selected from triethylenediamine, bisdimethylaminoethyl ether and bismorpholine diethyl ether; The organic metal catalyst is a mixture of one or more selected from stannous octoate, dibutyltin dilaurate, organic bismuth salts and organic antimony salts.
5. The degradable high-strength medical adhesive according to claim 1, characterized in that: The preparation method of the triol modified by the polyethylene glycol carboxylic acid derivative comprises the following steps: (1) reacting a polyethylene glycol carboxylic acid derivative with a hydrogen extraction reagent under the action of a first catalyst, and simultaneously introducing a benzyl protecting group to obtain an intermediate product I; (2) reacting the intermediate product I with a triol under the action of a second catalyst and a condensing agent to obtain an intermediate product II; (3) The intermediate product II is subjected to hydrogenation catalysis under the action of a third catalyst to obtain the triol modified with the polyethylene glycol carboxylic acid derivative.
6. The degradable high-strength medical adhesive according to claim 5, characterized in that: In step (1), the molar ratio of the polyethylene glycol carboxylic acid derivative, the first catalyst, the hydrogenation reagent, and the benzyl protecting group is (1-2): (1-2): (1-1.5): (1-3); the first catalyst is triethylamine, the hydrogenation reagent is sodium hydride, and the reagent providing the benzyl protecting group is 4-methoxybenzyl chloride; In step (2), the molar ratio of the intermediate product I to the triol, the second catalyst and the condensing agent is 1:(0.2-0.3):(0.2-0.35):(1-1.5); the second catalyst is 4-dimethylaminopyridine; and the condensing agent is 1,3-dicyclohexylcarbodiimide.
7. The degradable high-strength medical adhesive according to claim 1, characterized in that: The preparation method of the bis(2-hydroxyethyl)-N-methyl-N-trifluoromethylammonium iodide is to modify N-methyldiethanolamine under the action of fluorine-containing halogenated hydrocarbons; Wherein, the fluorine-containing halogenated hydrocarbon is trifluoroiodomethane, and the molar ratio of the N-methyldiethanolamine to the fluorine-containing halogenated hydrocarbon is 1:(1-2).
8. A method for preparing a degradable high-strength medical adhesive according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1: mixing component A and component C, heating and dissolving them, and then adding the third catalyst and component B to obtain a mixed reaction system; S2: After the reaction is complete, the temperature is lowered, and a rheology regulator, a foaming catalyst and a stabilizer are added to the mixed reaction system. After mixing evenly, the degradable high-strength medical adhesive is obtained.
9. The method for preparing a degradable high-strength medical adhesive according to claim 8, characterized in that: In step S1, the mixing heating temperature is 75-85°C, and the heating reaction time is 1-2 hours; the third catalyst is N,N-methylenebisacrylamide, and the molar ratio of the third catalyst to the component B is 1:(750-1500); In step S2, the cooling temperature is ≤15°C.
10. Use of a degradable high-strength medical adhesive as claimed in any one of claims 1 to 7 in a functional composite material.
Citation Information
Cited By
H2S concentration system
CN121222250A